MOBILITY OF EMPLOYEES AND STUDENTS IN A UNIVERSITY TOWN IN A POST-COMMUNIST COUNTRY - Josef KUBÍK; Ottó BARTÓK; Tomáš URBÁNEK (Transport Problems)
Transportation is undergoing its most significant transformation since the inception of road transport. This transformation is fueled by concerns about climate change and technological advancements. Understanding the current situation in medium-sized cities across Europe is crucial to developing transportation concepts for urban areas within the EU. This study offers insights into the current state of urban mobility in post-communist countries and depicts the current spatial mobility in a medium-sized city. The aim of this study is to evaluate the influence of selected socioeconomic factors on the mobility of employees and students. This study, conducted in 2019, employed quantitative research methods, including a questionnaire survey. In total, 545 employees and students participated in the survey, representing a significant indicator of mobility in the city of Zlín. Data analysis was performed using nonparametric methods. The results indicate a relationship between respondents’ job classification, age group, transportation time, and choice of means of transport. These findings can be applied to countries with similar historical and cultural development backgrounds, such as Poland, Hungary, and Slovakia.